A multi-rotor medium-voltage wind turbine system and its control strategy. (March 2022) - You, Rui; Yuan, Xibo; Li, Xueqing
Abstract: With the continuous increase in wind turbine power ratings, the growing turbine size makes the turbine manufacture, transport and installation more challenging. At MWs power level, the conventional two-level converters with a 690V voltage have to handle very high current, which causes substantial losses and high cost of power cables, switchgears, etc. To solve this issue, a multi-rotor medium-voltage modular wind turbine configuration is proposed in this paper. Each cell is composed of a turbine rotor, a permanent magnet synchronous generator (PMSG) and a converter. Each PMSG is driven directly by each rotor. The input and output power stages of each converter consist of a three-phase active rectifier and an H-bridge inverter. H-bridge inverters are connected in series to achieve medium-voltage grid connection. This wind turbine configuration has advantages such as more wind power capture, higher reliability, lower transport and installation cost, easy extension to higher power and grid voltage ratings and fault-tolerant operation capability. A control strategy of the wind turbine with maximum wind power capture is proposed. An imbalance compensation control scheme is also proposed to keep three phase output current balanced. Simulation results and experimental tests have validated the proposed wind turbine topology and control strategy.